A dual-axis tracking photovoltaic power plant as an educational tool. Issue 3 (July 2017) - Frankovic, Dubravko; Kirincic, Vedran; Valentic, Vladimir
Renewable energy sources have become a considerable part of electric transmission networks as well as medium and low voltage distribution networks. Understanding the overall process from design stage up to the installation stage, followed by the commissioning and startup of renewable energy sources plants is essential knowledge that electric engineers nowadays should posses. Therefore, in the first part of the article activities, conducted at the Faculty of Engineering, University of Rijeka, Croatia, necessary for the installation of a fully operational, grid connected photovoltaic power plant with dual-axis tracking system have been described. Consequently, upon photovoltaic plant's installation and commissioning, students are able to have 'hands-on' on a fully functional photovoltaic power plant and perform supervised, 'live' measurements and compare it with previously calculated values. Therefore, new – dedicated laboratory sessions have been introduced in an existing subject to make the most of the photovoltaic installation in the teaching process. In the second part, the article is mainly focused on the newly introduced laboratory sessions as well as on the educational framework and methodology. Some of the experiments that our students are able to perform include alternating current and direct current operating values measurements (photovoltaic string and inverter voltages, currents, power, efficiency, etc.), environmental parameters measurements (irradiance, air temperature, wind direction, velocity, etc.) and grounding parameters measurements (soil resistivity, photovoltaic plant's grounding resistance). The acquired knowledge gained from the activities performed during our educational photovoltaic plant project realization give us the ability to propose a methodology that can be used as the key model for other universities and faculties.